Some mesostigmatic mites (Acari: Parasitiformes) of Khuzestan Province, southwestern Iran - Sara Farahi; Parviz Shishehbor; Alireza Nemati (Persian Journal of Acarology)
Animal droppings constitute an ephemeral habitat where specialized invertebrate communities including significant abundance of mites live together. In order to study the Mesostigmata mites associated with manure, samples were taken from different manure types of domestic animals and poultry in Ahvaz and its vicinity in Khuzestan Province, southwestern of Iran, over a period of two years (2015-2017). Here we report 20 species belonging to eight families of Mesostigmata, among which 14 species are new records for the fauna of Khuzestan Province. The genus and species Leitneria pugio (Karg, 1961) is newly recorded from Iran. The genus and species were previously only recorded in Europe. Also, Uroobovella varians Hirschmann & Zirngiebl-Nicol, 1962 is recorded for the first time from Iran based on deutonymph stage. We further provide collection data for each species along with a key for known Iranian species of the genus Uroobovella.